PROSES BERPIKIR ALJABAR DALAM MENYELESAIKAN MASALAH MATEMATIKA BERBASIS OPEN-ENDED - Siti Nurcholifah; Riawan Yudi Purwoko; Heru Kurniawan (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2021)
This study aims to describe the algebraic thinking process of students in solving open-ended mathematical problems. The research method used was literature review through books, journals, and similar previous research. The results of the study of various literature are that there are three processes in thinking algebra when students are faced with open-ended based problems including understanding patterns, representing, and solving. In the first stage is, understanding patterns students understand the patterns shown by writing important statements in the problem or stating the patterns in the form of images. At the stage of representing students doing symbolic manipulation of patterns in the form of equations containing coefficients, variables, and constants. At the stage of completing students use the right strategy so that a variety of alternative answers correct. Open-ended can be seen when students go through the stages of understanding patterns and completing.